Impulse Buying on users of online shopping - Orfyanny S. Themba; Aminuddin Hamdat; Nur Alam; Karta Negara Salam (Jurnal Manajemen Bisnis, 2021)
This study explores the effect on impulse buying of hedonic motivation for shopping, shooping lifestyle and price discount. In this type of non- probability sampling method used in the study, the collection of data using a questionnaire instrument is judgmental sampling to Lazada.co.id for as many as 100 consumers. With the assistance of the SPSS unit, the type of analysis used is multiple linear regression. The results of this study show that hedonic motivation for shopping, shopping lifestyle and price discount have a significant impact on the purchase of impulses on Lazada.co.id Online Shopping Consumers.